Characteristics of the karyotype of Ukrainian buffalos - Starodub, Lyubov; Mokhnachova, Nataliia (Buffalo Bulletin, 2023)
The article presents the results of studying the karyotype of the Ukrainian buffalo population. With the help of routine and GTG methods of analysis of metaphase plates of chromosomes, it was established that in the studied animals the diploid chromosome set was equal to fifty chromosomes (2n=50), which consisted of 5 pairs of meta- and submetacentric and 19 pairs of acrocentric autosomes and one pair (XX) or (XY) sex chromosomes. The total number of chromosome arms (FN) was 60, which correspond to animals of the water buffalo species (Bubalus bubalis), a subspecies of the river buffalo (B. b. Bubalis). Cytogenetic control revealed wide intraspecies limits of spontaneous somatic mutagenesis: absence of constitutive chromosomal disorders; the frequency of metaphases with aneuploidy, the average value (M±m) of which was equal to 10.5±0.13%, polyploidy (M±m=0.7±0.25%), asynchronous separation of the centromeric regions of chromosomes - (M±m=5.3±2.00), chromosomal breaks (M±m=0.7±0.24%), the proportion of cells with micronuclei (M±m=2.5±0.39‰), binucleated cells (M±m=2.6±0.32‰) and mitotic index (M±m=4.8±0.65‰). It has been established that Ukrainian river buffaloes are characterized by high karyotype stability.